2016
DOI: 10.1080/2162402x.2016.1255394
|View full text |Cite
|
Sign up to set email alerts
|

Immune contexture and histological response after neoadjuvant chemotherapy predict clinical outcome of lung cancer patients

Abstract: There is now growing evidence that the immune contexture influences cancer progression and clinical outcome of patients with non-small cell lung cancer (NSCLC). If chemotherapy is widely used to treat patients with advanced-stage NSCLC, it remains unclear how it could modify the immune contexture and impact its prognostic value. Here, we analyzed two retrospective cohorts, respectively composed of 122 stage III-N2 NSCLC patients treated with chemotherapy before surgery and 39 stage-matched patients treated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 38 publications
3
63
1
Order By: Relevance
“…However, high tumor islet/stromal macrophage ratio was significantly associated with longer DFS and OS (187). In a French study of 122 stage III-N2 NSCLC patients treated with cisplatin-based chemotherapy, no correlation of CD68+ TAMs with survival rates was found (188). These data indicated TAMs located in tumor nest (islets) as a favorable prognostic factor after platinum-containing chemotherapeutic treatment.…”
Section: Tams and Lung Cancer Treatmentmentioning
confidence: 98%
“…However, high tumor islet/stromal macrophage ratio was significantly associated with longer DFS and OS (187). In a French study of 122 stage III-N2 NSCLC patients treated with cisplatin-based chemotherapy, no correlation of CD68+ TAMs with survival rates was found (188). These data indicated TAMs located in tumor nest (islets) as a favorable prognostic factor after platinum-containing chemotherapeutic treatment.…”
Section: Tams and Lung Cancer Treatmentmentioning
confidence: 98%
“…In the Kras LSL−G12D/+ Trp53 −/− (KP) genetically engineered mouse model of lung cancer, hypo-fractionated radiotherapy induces an early reduction in TLS densities followed by their restoration within 2 weeks 119 . Two independent studies of human NSCLC reported that TLSs present in lesions regressing after neoadjuvant anti-PD1 therapy 30 or chemotherapy 120 were associated with longer disease-free survival and overall survival 120 . By contrast, caution should be taken with using associated therapies, such as corticosteroids, often used to manage the side effects of chemotherapy, as they have been reported to decrease TLS density in lung squamous cell carcinoma and to impair the positive clinical impact 60 .…”
Section: Therapeutic Modulation Of Tlss and Its Impact On Clinical Oumentioning
confidence: 99%
“…However, the widespread use of these treatments has been implemented mostly on empirical (rather than immunological) grounds. 200,[296][297][298][299][300] Indeed, the possibility that chemotherapy and other forms of treatment (including radiotherapy and photodynamic therapy) might promote an immunogenic form of cancer cell death has been overlooked for several decades. [301][302][303] Thus, current anticancer drugs have been developed in immunodeficient preclinical models and in clinical trials devoid of any form of immunomonitoring, mainly most often aimed at identifying maximum tolerated doses (MTDs).…”
Section: Discussionmentioning
confidence: 99%